Contratos existenciais: revisitando os elementos contratuais à luz de uma hermenêutica emancipatória - Menezes, Caroline Nogueira Teixeira de (2016)
The present work proposed to develop the new dichotomy presented by the author Antônio Junqueira de Azevedo, namely profit contracts and existential contracts, in light of an emancipatory hermeneutics. Said that, the theory of legal business is revisited in a way to propose the construction of elements and assumptions particular of the existential contracts in order that this classification becomes able to be used as a parameter to assist the interpretation and application of law when against one juridical relationship of contractual nature, whom object is the human subsistence. To do so, the work was based on an interdisciplinary vision to demonstrate how the changes on the social environment, just like the function of the intellectuals, influenced on the construction of this new dichotomy proposed. The transition of the legislators’ function to society interpreters between the modernity to the postmodernity, without representing a break, imposed the impression that the contract ought to be seen more than a free economics game instrument between two contractors, but also a precious tool for the guardianship and promotion of the human person and even for its emancipation. In this context, the existential contract claim a diverse treatment for the effective protection of these contractors, once the judges have to ensure this fundamental needs. This doesn’t reclaim the contempt for the Market neither of its social function on the society. After all, it is also responsible for the assurance of some fundamental rights. That diverse and qualitative treatment imposes itself because the vulnerability of these subjects gets recognized by means of the contracted object´s essentiality. This mean to propose one extension of the vulnerability beyond the consumer, in a way to protect other people that find themselves in a similar inequality situation. Thereby, the vulnerability principle becomes one effective tool to supply the emancipatory flaws of the legal framework these new disadvantaged subjects. For the achievement of this work, the method of deductive approach has been adopted, because the base is the analysis of the Theory of the general legal Business for the construction of elements and assumptions of existential contracts. Thus, the argumentative method has been used to justify the extension of the principle of vulnerability, as to get a better approach of the existential contracts in the concrete case. In this context, the monographic procedure method has been used. It involves bibliographical and jurisprudential research. The technical procedures adopted were the theoretical and qualitative analysis, as the study aimed to deepen the comprehension of the private institutes based on the person’s dignity by the law applicators. This focus on them becoming able to use this new hermeneutics proposed in a concrete case.